The Impact of Biofuel Intensification on Integrated Climate-Land-Energy-Water System - Moristanto; Erick Hutrindo; Catur B Kurniadi; Adrianus Amheka (Pusbindiklatren Bappenas, 2022)
Producing biodiesel using a mixture of palm oil is one of the main policies today. This paper studied the interactions among climate, land, energy, and water in a model to address national biofuel intensification policies and identified biofuels’ role in fulfilling energy needs, the trade balance, and reducing greenhouse gas emissions. The integrated climate land energy system (CLEWs) model was employed here. The model simulated the implementation of B30 in 2020 (B30/20), B40/25, and B50/30. The results showed that the implementation of the B30/20, B40/25, and B50/30 scenarios requires 15.30, 20.20, and 25.10 million tons of Crude Palm Oil (CPO), respectively. In terms of land, implementing the B30/20, B40/25, and B50/30 scenarios needs an additional 8.36, 69.33, and 80.38 thousand km2 of oil palm plantations, respectively 2030. In terms of emission, implementing the B40/25 and B50/30 policies can reduce 160 MTon and 320 MTon CO2-eq, respectively by 2030. There is no irrigation system needed in oil palm plantations. The paper recommended that the biofuel incentives or need price mechanism formulation and land allocation policies by using marginal/critical land for new oil palm plantations. The policy should be used to improve the yield or crop productivity of palm oil plants.